2022
DOI: 10.1016/j.jsps.2022.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Diets and dietary supplements used during the COVID-19 pandemic in the United Arab Emirates: A cross-sectional survey

Abstract: Introduction Since the beginning of the Coronavirus disease 2019 (COVID-19) pandemic, there has been a marked increase in the use of diets and dietary supplements (DDS) for the prevention and treatment of this emerging disease. While DDS are generally regarded as harmless, little evidence exists on the safety and efficacy of their use for COVID-19. Objectives To investigate the pattern and determinants of DDS use among the United Arab Emirates (UAE) population for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 55 publications
15
27
0
Order By: Relevance
“…Concerning the socio-demographic characteristics of respondents of this survey ( Table 1 ), the majority of them were women (approximately three quarters), which is consistent with the previous research of phytotherapy use in COVID-19 patients from various regions [ 19 , 20 , 21 , 22 , 23 ]. The present study also mainly included respondents with college and university degrees (4.23% and 63.38%, respectively), which is similar to previously reported results [ 19 , 21 , 22 , 23 , 24 , 25 ]. The majority of interviewees were employed, which is consistent with previously conducted studies of phytotherapy and various CAM uses against COVID-19 [ 19 , 20 , 22 , 23 , 24 , 25 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Concerning the socio-demographic characteristics of respondents of this survey ( Table 1 ), the majority of them were women (approximately three quarters), which is consistent with the previous research of phytotherapy use in COVID-19 patients from various regions [ 19 , 20 , 21 , 22 , 23 ]. The present study also mainly included respondents with college and university degrees (4.23% and 63.38%, respectively), which is similar to previously reported results [ 19 , 21 , 22 , 23 , 24 , 25 ]. The majority of interviewees were employed, which is consistent with previously conducted studies of phytotherapy and various CAM uses against COVID-19 [ 19 , 20 , 22 , 23 , 24 , 25 ].…”
Section: Resultssupporting
confidence: 88%
“…The present study also mainly included respondents with college and university degrees (4.23% and 63.38%, respectively), which is similar to previously reported results [ 19 , 21 , 22 , 23 , 24 , 25 ]. The majority of interviewees were employed, which is consistent with previously conducted studies of phytotherapy and various CAM uses against COVID-19 [ 19 , 20 , 22 , 23 , 24 , 25 ]. Regarding marital status, most of the participants were married, again in accordance with the results of other studies [ 20 , 24 , 25 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Studies describing prevalence of CAM use during the COVID-19 pandemic are still sparse, but an Irani study reported 84% use [12], and a Ghanian study reported 85.5% use of CAM during COVID-19 outbreak [13]. In Saudi Arabia 93% of the population reported to use natural or herbal products during the COVID-19 [14] while 56.6% in United Arab Emirates reported use of dietary supplements for prevention or treatment of COVID-19 [15]. A Polish study found increased consumption of dietary supplements during the first wave of the COVID-19 pandemic [16], and in Cameroon did 24.4% of the studied population use herbal medicine for COVID-19 prevention [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, not much data supported the intake of oral vitamin C supplements to increase immunity ( 13 ). Several studies have shown that oral vitamin C supplementations since COVID-19 have increased ( 15 , 16 ). However, dietary supplements in those studies against COVID-19 were not evidence-based.…”
Section: As Daily Supplements–prevention Measuresmentioning
confidence: 99%